(untitled) (Human Factors in Design, 2013)
The increase in life expectancy of the Brazilian population has raised awareness about the importance of studying the needs and difficulties of elderly individuals in their everyday activities. Thus, the aim of this paper is to discuss the development of new products for bathroom and toilet environment - especially during the informational phase of the project. The study focused on elderly users needs and demands by analyzing: function, usage and ergonomic aspects of the products available in the market. For this purpose, a field survey was performed at the Oscar José Pithan Shelter, located in Santa Maria-RS. Direct observation and semi-structured interviews were used to understand and record the use of bathroom and toilet environment by the target audience. The research provided subsidies/support for the development of new products especially during the informational and conceptual project phases that indicated description for the Final Product Project.